2015
DOI: 10.1007/s00601-015-1007-7
|View full text |Cite
|
Sign up to set email alerts
|

Semileptonic Decays of $${\Xi_{b}}$$ Ξ b and $${\Sigma_{b}}$$ Σ b Baryons via the Three-Body Variational Approach

Abstract: We consider a nonrelativistic three-body system with a Cornell interaction in hyperspherical formalism. In order to obtain the solution of the system, we use the improved variational method. Next, we investigate the Isgur-Wise function and thereby report the semileptonic decay width of bottom baryons b and b . We report the branching ratios and partial decay widths as well and make a comparison with present data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…In recent years, the thermodynamics properties of quantum systems [84][85][86][87][88][89], the quantum Hall effect [90][91][92] and the possibility of building coherent states [93][94][95][96] and displaced Fock states [97,98] have attracted a great interest in the literature. It is well-known in nonrelativistic quantum mechanics that the Landau quantization is the simplest system that we can work with the studies of the quantum Hall effect, while the harmonic oscillator is used in the studies of coherent states.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the thermodynamics properties of quantum systems [84][85][86][87][88][89], the quantum Hall effect [90][91][92] and the possibility of building coherent states [93][94][95][96] and displaced Fock states [97,98] have attracted a great interest in the literature. It is well-known in nonrelativistic quantum mechanics that the Landau quantization is the simplest system that we can work with the studies of the quantum Hall effect, while the harmonic oscillator is used in the studies of coherent states.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that the DO has been extensively studied, for example, in (1 + 1)-dimensions [32][33][34], in (2 + 1)-dimensions [35,36], in the cosmic string spacetime [37][38][39], in an Aharonov-Casher system [40], in a rotating frame of reference [41], in thermodynamic properties [42,43] and in the context of gravity's rainbow [44].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the DO and KGO oscillators have been the subject of research on thermodynamic properties, as shown in Refs. [57,58,77]. Therefore, the systems analyzed in this work can be a starting point for investigating the influence of the pointlike global monopole on the thermodynamic properties.…”
mentioning
confidence: 99%
“…Two interesting points are the possibility of building coherent states [33][34][35][36] and displaced Fock states [37,38]. Another topics for discussion are the Aharonov-Bohm effect for bound states [39][40][41][42] and the thermodynamics properties of quantum systems [43][44][45][46][47][48].…”
Section: Discussionmentioning
confidence: 99%